Modification of a gray-level dynamic range based on a number of binary bit representation for image compression - Arief Bramanto Wicaksono Putra; Supriadi Supriadi; Aji Prasetya Wibawa; Andri Pranolo; Achmad Fanany Onnilita Gaffar (Science in Information Technology Letters, 2020)
The unique features of an image can be obtained by changing the gray level by modifying the dynamic range of the gray level. The gray-level dynamic range modification technique is one technique to minimize the selected features.  Bit rate reduction uses coding information with fewer bits than the original image (image compression). This study using the dynamic level of the gray level of a modified image with the concept of binary bit representation or also called bit manipulation.  Using some binary bit representation options used: 4, 5, 6, and 7 of bit can obtain the best compression performance. Measurement of compression ratio and decompression error ratio to a benchmark comparison called compression performance, which is the ultimate achievement of this study. The results of this study show the use of 6-bit binary representation has the best performance, and the resulting image compression does not resize the resolution of the original image only visually looks different.